Long-term effect of plastic feeding on growth and transcriptomic response of mealworms (Tenebrio molitor L.). (January 2022) - Zhong, Zheng; Nong, Wenyan; Xie, Yichun; Hui, Jerome Ho Lam; Chu, Lee Man
Abstract: Plastic waste has been considered a serious global environmental problem for decades. Despite the high recalcitrance of synthetic plastics, the biodegradation of polyethylene (PE), polystyrene (PS), polypropylene (PP), and polyvinyl chloride (PVC) by some insect larvae has been reported; however, the mechanism of degradation remains largely unknown. We investigated the effects of plastics on the growth of mealworms (larvae of Tenebrio molitor ) and their role in PS and PE degradation. Mealworms were capable of ingesting high-impact polystyrene (HIPS), expanded polystyrene (EPS) and low-density polyethylene (LDPE) but not linear low-density polyethylene (LLDPE) or polypropylene (PP). Plastic consumption was negatively dependent on plastic crystallinity. Transcriptome analysis and KEGG mapping revealed that mealworms act as downstream decomposers in plastic depolymerization and that fatty acid degradation pathways may play important roles in the digestion of plastic degradation intermediates produced by gut bacteria. In addition, PS and PE degradation was achieved via the diffusion of extracellular depolymerases, which probably acted on the distal backbone and produce shorter linear chains that containing ≤16 C atoms instead of branched chains. Additionally, the intermediates of PS degradation are expected to be further decomposed by mealworms as xenobiotics. This study provided a preliminary understanding of plastic degradation mechanism by mealworms. Graphical abstract: We studied the mechanisms of recalcitrant plastic degradation by mealworms, which have potential benefits on waste management. Image 1 Highlights: We studied effects of plastics on mealworm growth and its mechanism in PS and PE degradation by transcriptomic analysis. Plastic consumption was negatively dependent on plastic crystallinity. Fatty acid degradation pathway was important in the digestion of plastic degradation intermediates. Depolymerases probably act on the distal backbone and produce shorter linear chains that containing ≤16 C atoms. Intermediates of PS degradation were further decomposed by mealworms as xenobiotics.